Evaluation of Flower of Barleria Prionitis for Anti-Inflammatory and Anti Nociceptive Activity - SUNIL K. JAISWAL; MUKESH K. DUBEY; SANJEEB DAS; ARTI R. VERMA; M.VIJAYAKUMAR; CHANDANA V. RAO (International Journal of Pharma and Bio Sciences, 2010)
Traditionally aerial parts of Barleria prionitis Linn. has been used in the inflammation, fever & toothache. The present study was undertaken to evaluate the anti-inflammatory and anti-nociceptive activity of 50% ethanolic extract of the flower of B. prionitis (BPF) in experimental animals. The BPF in doses of 50, 100 and 200 mg/kg caused a dose-dependent inhibition of swelling caused by carrageenin equivalent to 17.8–48.6% protection (P>0.05–P<0.001) and in cotton pellet granuloma, 46.2–36.4% protection (P<0.01-P<0.001) was observed from inflammation. There was a significant increase in analgesio meter force induced pain in mice equivalent to 26.3–48.23% protection (P<0.01P<0.001) & 5.24 - 34.6 % (P<0.05–P<0.001) protection against Acetic acid induced writhing. Our results shows that flower of B. prionitis possess significant anti-inflammatory and anti-nociceptive activity.